Examining of the novel in the senior secondary phase (English first language higher grade): a study of conflicting aims - Macrae, Claire Elisabeth (Rhodes University, Faculty of Education, Department of Education, 1989)
This study deals with the problems of external examining, the inflexible demands of which dominate and dictate to literature teaching in South African schools today. The aims of teaching literature are discussed, and it is suggested that the negative attitudes among pupils resulting from the present examining system defeat many of these aims. The opportunities for the enjoyment of literature are minimised by the process of preparation for external examinations. Creative teaching methods are abandoned in favour of coaching for specific types of questions, which are determined and limited by the practical constraints of a mass external examination. In catering to the demands for admininstrative reliability and efficiency, the educational validity and efficiency of the examinations are sacrificed. In Britain the Newbolt and Bullock Reports, among others, have made forceful recommendations for alternative approaches to external examining. Subsequently, much experimentation with internal examining, course-work and open-book examining has followed, aspects of which are discussed in this study. There has been limited experimentation in these areas in South Africa. The TED conducted a successful internal examining experiment in English literature, the results of which are considered in this thesis. The national English Olympiad open-book examination is a further example of the success of an alternative approach. By contrast, a comparison of examination papers set by the JMB and CED over the last ten years, shows clearly that the stated syllabus aims of teaching literature and the aims of examining the subject were wholly incompatible. Recommendations are made for the adoption of alternative examining strategies in order to address the shortcomings identified
Keywords: Education, Secondary; English -- Study and teaching (Secondary) -- South Africa; Education, Secondary -- Evaluation